Foreign Direct Investment And Sustainable Development Of Four Asean Members - Idris Merican, Yasmine Merican (2007)

(untitled)
This study attempts to answer the research question of what and to what extent are the economic (growth), social (inequality), and environmental (pollution) impacts of foreign direct investment (FDI) in the four Southeast Asian nations (ASEAN-4). The next question is how well the results of the study fit the theories of FDI from both the neo-classical cum neo-liberal theories, dependency theory, and the pollution-haven hypothesis (PHH) perspective. Employing the time-series analyses utilizing the Autoregressive Distributive Lag (ARDL) technique suggest that the FDI does better than domestic investment at promoting growth levels in Malaysia, Indonesia but not for Thailand and the Philippines where the reverse is true. Hence, neo-liberal theory is supported in Malaysia and Indonesia while dependency theory is supported in Thailand and the Philippines. In terms of inequality, FDI improves income inequality in Malaysia and Indonesia but worsens inequality in Thailand and proved insignificant for the Philippines. Neo-liberalism is supported in Malaysia and Indonesia while dependency is supported in Thailand. However, Philippines is neutral to either school of thought. Environmental wise, the PHH which postulates that lower environmental standards in host-developing nations attract FDI from their developed countries of origin is supported in Malaysia, Thailand, and the Philippines but not in Indonesia where FDI is inversely related to pollution. Hence, the neo-liberal claim that FDI via multinationals brings cleaner technology to host developing nations is contested in these three nations but could be supported in Indonesia. The differences in the study’s findings could be attributable to the differences in FDI inflows’ composition itself. Malaysia’s FDI inflows mainly went to the secondary and followed by the primary sector and a trickle flowed into the tertiary sector. Thailand had slightly more FDI inflows into the tertiary sector as opposed to the secondary and far less into the primary sector. Indonesia’s FDI inflows mainly resided in the manufacturing sector, followed by the tertiary and primary sectors. Philippines had about equal FDI share in the primary and secondary sectors with the tertiary receiving the majority share.